Mitigating the impact of the Mount Semeru eruption in Lumajang regency using a Geographic Information System Approach - Dani, Ilham; Rasimeng, Syamsurijal; Amalia, Firda (Teknisia, 2024)
Indonesia is a country with high volcanic activity, with more than 130 active volcanoes. Mount Semeru is the highest volcano on the island of Java, which is located between Malang Regency and Lumajang Regency. Mount Semeru's volcanic activity can cause disasters such as lava flows, poisonous gas, volcanic ash ejections and rock avalanches. Mitigation of volcanic eruption disasters in Lumajang Regency is carried out by mapping areas that are potentially affected. This research aims to examine the use of Geographic Information Systems (GIS) in mapping areas affected by the eruption of Mount Semeru. The method used is GIS-based spatial analysis to identify areas prone to volcanic eruptions, which are divided into three zones based on their level of vulnerability. The mapping results show that Pronojiwo and Pasrujambe District has the highest level of vulnerability, followed by Candipuro and Senduro Districts.